PENETAPAN KONSENTRASI PUPUK ORGANIK CAIR UNITAS SUPER YANG TEPAT PADA TANAMAN CABAI RAWIT LOKAL (Capsicum frutescens L.) - Jamilah Jamilah; Hamdani Nusri; Zahanis Zahanis; Milda Ernita (Universitas Lambung Mangkurat, 2018)
The objective of the study was to obtain the proper concentration of POC Unitas Super on the optimal growth and yield of local cayenne pepper (Capsicum frutescens L.). The experiment was conducted at Kanagarian Toboh Gadang, Padang Pariaman, from July to October 2017. The location is at 20 m asl, and is 10 km from the district capital, in the dry land of latosol soil type. The tools used are the hoe, stand, rope, bucket, analytical scale, meter, rake, and stationery. Materials needed include; local cayenne pepper seedlings result from propagation of local cayenne pepper seeds, POC Unitas Super (US) obtained from Faculty of Agriculture Universitas Tamansiswa Padang. NPK Compound Fertilizers (15-15-15) are given 50% recommendation, and manure as much as 5 ton ha-1. The experiment was conducted using Completely Randomized Design, with 5 treatment of POC concentration ie; P0 (0 ml L-1); P1 (25 ml L-1); P2 (50 ml L-1) and P3 (75 ml L-1), replicate 4 times, so there were 20 experimental units. The data obtained were analyzed statistically by using F (ANOVA) test of 5% real level if the treatment had the significant effect on BNT further test (smallest real difference) at 5% level. The parameters observed were; plant height, number of branches, the diameter of plant canopy, the age of flowering, the yield of cayenne pepper. The giving of 50 ml of L-1 POC Unitas Super every 2 weeks is the optimum concentration to increase the growth and yield of cayenne pepper (Capsicum frutescens L.). The production of cayenne pepper produced reached 5.55 kg plot-1 or equal to 55.50 tons ha-1.